Effect of Ozone Pretreatment on the Microleakage of Class V Cavities Following Office Bleaching with Diode Laser - Derya Surmelioglu; Eda Erbil; Emine Şirin Karaarslan; Osman Demir (Cumhuriyet University, 2018)
Objective: This study investigated the effect of ozone treatment on the microleakage of class V composite restorations after using two different bleaching agents with laser activation. Materials and Methods: Forty non-carious maxillary central incisor teeth extracted for periodontal disease were used and randomly divided into two main groups. Group 1: Bleaching agent including 40% H2O2 was activated with laser (Diode 980 nm, Gigaa Dental Laser Cheese, China). Group 2: Bleaching agent including 35% H2O2 was activated with the same laser. Then, the teeth were randomly divided into two subgroups (n=10). Ten specimens in each subgroup were subjected to ozone treatment (Ozonytron XP-OZ, MIO International, Germany) for 30 seconds, while the remaining left untreated/remainings were control group. After class V cavity preparation on the buccal surfaces, all cavities were filled with composite resin (Filtek Z550, 3M ESPE, USA). Following thermal cycling (5-55°C, 5000×), the specimens were subjected to dye penetration within 0.5% basic fuchsine for 24h. Then, the teeth were sectioned longitudinally to evaluate staining and the depth of staining along with the tooth-restoration interface was recorded with a stereomicroscope.  Results: There were no significant differences between the two bleaching agents in microleakage of restorations (p > 0.05). The ozone treatment didn't decrease the microleakage values (p > 0.05). There were significant differences among the scores of microleakage at the enamel and gingival margins  (p < 0.05). Conclusion: Ozone treatment did not affect microleakage values of class V composite restorations after dental bleaching.